Comparison of Age-Related Anthropometric Changes Among Elderly Punjabi Males Residing in Old-Age Homes with Those Residing with Their Families. Issue 1 (June 2020) - Singh, K.; Singh, S. P.; Kaur, G.; Bose, K.
Abstract: The present study was conducted to find out the changes in anthropometric measurements with advancing age among elderly males living in old-age homes and those living in family. Cross-sectional data on anthropometric measurements and other general information were obtained for 400 male subjects (200 living in old-age homes and 200 living with family) ageing 60 years and above, and data were collected from various districts in Punjab. Height decreased non-significantly and sitting height decreased significantly ( p = 0.03) from 60 years to ≥80 years of age in both the groups of elderly males. Weight decreased significantly among the elderly males residing in old-age homes ( p < 0.001). Biceps ( p = 0.03) and thigh skinfold ( p = 0.009) thicknesses decreased significantly only among elderly residing in old-age homes. Abdominal ( p = 0.01) and supra-iliac ( p = 0.01) skinfold thickness measurements decreased significantly among elderly residing with their families. Circumference measurements on limbs decreased significantly ( p < 0.01) among both the groups of elderly (except upper arm circumference among elderly residing with their families). Abdominal circumference decreased significantly ( p = 0.04) among the elderly males residing with their families. Elderly residing in old-age homes retained more abdominal subcutaneous fat mass and lost more appendicular fat mass as compared with those residing with their families. Elderly residing with their families lost lesser appendicular muscle mass as compared with their counterpart's elderly residing in old-age homes.